THE SPECIFICS OF THE MOUNTAIN BIKE - DOWNHILL CASE STUDY DH FLOW RIDE COMPETITION BISTRIȚA - Leonida Horea ȘTEFĂNESCU; Eleonora ZĂGREAN (Cluj University Press, 2022)
Specialized articles and publications reveal the impact that mountain biking registers worldwide today in the field of outdoor sports and mobility. The aforementioned field is under rapid development, a fact revealed by the increasing number of practitioners, the competitions organized throughout all continents, addressing a wide range of ages and proficiency categories, from amateurs to high-performance professional athletes. Mountain biking is gaining popularity in Romania as well, where several competitions (Enduro, Downhill, Cross) are organized, engaging numerous competitors. Most of the locations where downhill skiing is practiced (and mechanical means of ascent are present, especially chairlifts) have become areas adapted for practicing mountain biking in the off-season.